Executive functions in the regulation of university learning - Gualpa-Naranjo, Kenneth (2019)
This research carried out a correlational analysis between executive functions (conduct with initiative, capacity planning and ability to supervise and monitor cognition) and self-regulation of learning (management of planning and management of motivation) in a sample of 203 university students between 18 and 25 years of age (Mage = 20.53, SD = 1.77), 109 men (53.7%) and 94 women (47.3%). In the results, significant relationships were found between: management of motivation and capacity planning (r = .49, p = <.001), management of motivation and conduct with initiative initiative (r = .464, p = <.001), management of the planning and ability to supervise and monitor cognition (r = .51, p = <.001). No significant differences were found when comparing the dependent variables according to gender or marital status (t(201) = .07, p = .79), laterality (t (201) = 1.46, p = .22), gender or career ( x2(203) = 11.88, p = .04) and study time (x2(203) = 1.55, p = .46). As a conclusion, it is suggested that executive functions have a considerable correlation on the learning of university students, which, together with the selfregulation of learning, contribute significantly to the higher achievement of university students. The report is closed, highlighting the need to conduct more research in this area for the benefit of university students.